Development of a speed warning device for micro-mobility devices - Oh, Khee Wen (Nanyang Technological University, 2021)
Rapid urbanization in many developed countries has brought upon a significant increase in city traffic congestion. This has led to the rise of micro-mobility as it is seen as a more convenient form of personal transportation by the general public. However, as more people switch to using micro-mobility devices to travel around the city, there has been a serious surge in MMD-related accidents in Singapore over these few years. As a result, the Land Transport Authority has resorted to implementing strict regulations such as banning all Personal Mobility Devices and Power Assisted Bicycles from footpaths all together. This is a huge setback to Singapore’s goal of becoming a car-lite society where sustainable transport and future mobility is highly emphasized. Hence, this project aims to develop a speed warning device that will strive towards the reintroduction of Personal Mobility Devices and Power Assisted Bicycles and ensuring that they are safe for the sharing of pedestrian footpaths once again. This device will adopt the state-of-the-art object detection and tracking algorithm and will be able to operate as per normal in both bright and dark lighting conditions.